Parental education and the rising transmission of income between generations - Marie Connolly; Catherine Haeck; Jean-William Laliberté (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Groupe de recherche sur le capital humain (GRCH), 2020)
Intergenerational mobility has decreased over time for the cohorts of children born between the 1960s and the 1980s in Canada. At the same time, returns to education have gone up. Both factors have contributed to exacerbating income gaps between children of parents with and without secondary education. However, the transmission of residual parental income differences that cannot be accounted for by differences in educational attainment have increased at a faster rate than overall intergenerational income transmission. In addition, overall income mobility has shrunk less in communities that have experienced greater increases in parental high school completion rates over time. There is no significant relationship with changes in university education. Overall, these patterns suggest that fostering high school completion may help slow down the worsening of intergenerational income mobility.
Keywords: J62; D63; I24; I26; 330; social mobility; intergenerational income transmission; income inequality; education; Canada